Math, asked by yesua3735, 1 year ago

simplify 15 x minus 8 x cube + 3 x cube minus 8 x square - 4 - 2 X - 65 x cube minus 2 x

Answers

Answered by KunalTheGreat
9

Answer:

Let's simplify step-by-step.

15x−8x^{3}+3x^{3}−8x^{2}−4−2x−65x^{3}−2x

=15x+−8x^{3}+3x^{3}+−8x^{2}+−4+−2x+−65x^{3}+−2x

Combine Like Terms:

=15x+−8x^{3}+3x^{3}+−8x^{2}+−4+−2x+−65x^{3}+−2x

=(−8x^{3}+3x^{3}+−65x^{3})+(−8x^{2})+(15x+−2x+−2x)+(−4)

=−70x^{3}+−8x^{2}+11x+−4

Answer:

=−70x^{3}−8x^{2}+11x−4

:)

Step-by-step explanation:


Similar questions